Mechanism of soil breaking and prediction of pile diameter in silty clay by jet grouting using CFD-DEM coupling - Yiliang Yu; Hanlong Liu; Changbing Qin; Mingke Lin; Zhixiong Chen; Xuanming Ding (Computers and Geotechnics, 2026)

A tri-modal biosensor based on alkyne-functionalized gold nanoparticles and molecular beacon for detection of resistance-related point mutations in epidermal growth factor receptor-tyrosine kinase inhibitors - Ding Tan; Haixin Long; Ya Wang; Wenjing Lin; Yiling Huang; Haijun Chen; Yu Gao (Molecular Biology Reports, 2026)

Zinc-binding protein metallothionein 3 protects vascular smooth muscle cells from ferroptosis via blocking lysosomal degradation of GPX4 - Wenxin Lin; Xin Feng; Jingjie Chen; Bo Huo; Xian Guo; Molin Yang; Ding-Sheng Jiang; Linling Yu; Yue Chen (Journal of Molecular Medicine, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Selective recovery of palladium from actual acidic wastewater using a covalent triazine framework: The critical enabling role of chloride ions - Junyi Yu; Qingying Xiao; Ziwen Chang; Jianzhi Zhang; Hao Dong; Jiaochan Zhong; Lin Ding; Yidi Chen; Xubiao Luo; Penghui Shao (Water Research, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Seismic response of ultra-deep strata with weak interlayer reinforced by vertical rodin jet pile and dynamic compaction - Yiliang Yu; Hanlong Liu; Changbing Qin; Mingke Lin; Zhixiong Chen; Xuanming Ding (Engineering Geology, 2026)

Nitrite reductases: From structure–function relationships to biocatalytic nitrite depletion and detection - Lin Yuan; Fang Wang; Han Zhang; Shu-Yu Ding; Zhong-Hua Yang (Trends in Food Science & Technology, 2026)

Safety evaluation and probiotic properties of Bacillus velezensis YK-19 capable of degrading deoxynivalenol: In vitro characterization and in vivo safety assessment in mice - Yukai Lin; Jingjing Zhao; Bo Wen; Songbiao Chen; Lei Wang; Xiaojing Xia; Yanzhao Xu; Yanyan Jia; Rongxian Guo; Ke Shang; Zuhua Yu; Chengshui Liao; et al. (Food Bioscience, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Co-delivery of nitric oxide and MnO2 nanosheets via an injectable hydrogel for inflammation regulation and bone regeneration in periodontitis - Liwei Zhang; Jielin Lei; Xin Wang; Yaoben Wang; Jiandong Ding; Hongxiu Yu; Lin Yu (Chemical Engineering Journal, 2026)

Exosomal miR-21-5p from ectopic endometrial stromal cells drives fibrosis progression in endometriosis through direct VHL targeting - Jia-Hao Chen; Yi-Hong Lei; Dian-Chao Lin; Hua-Ying Zhang; Zhi-Xiong Huang; Ruo-Fan Huang; Pei-Tong Wei; Meng-Jie Yang; Xin-Yu Ding; Wei-Dong Zhou; Qiong-Hua Chen (Human Cell, 2026)

Multiscale molecular engineering of a thermogelling polymer integrating quantum mechanics, polymer chemistry and artificial intelligence - Tao Sun; Weihan Rao; Junyi Li; Lingxi Li; Yiman Wei; Shuquan Cui; Wenqian Li; Yanshuang Zhang; Yixuan Wang; Lin Yu; Jiandong Ding (Science Bulletin, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

A quasi-zero stiffness locally resonant metamaterial with tunable low-frequency and wide bandgap - Haibin Ding; Chenghui Lin; Changjie Xu; C.W. Lim; Zhiyun Liu; Yitian Yu; Lihong Tong (Engineering Structures, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Natural antimicrobial composite membranes for effective filtration and inactivation of airborne bacteria and viruses - Guangpeng Yao; Zhijian Liu; Jie Shi; Lina Hu; Mingtao Ding; Chaofan Lin; Wenbin Zhuang; Miao Yu; Junzhou He (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Unveiling the superior Pb(II) affinity of sulfonic acid in functionalized UiO-66: A per-functional-group quantification strategy - Shuiping Yu; Yu Luo; Zhiwei Jin; Wenbao Li; Xianglin Zhong; Honggang Zhang; Xinggang Liu; Lin Ding; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

Smart bearings enabled by the tribovoltaic effect and machine learning - Xiangtian Ding; Yiwei Zhou; Weiqi Wang; Shaoli Liu; Shujun Zhou; Anhui Yu; Jiacheng Cai; Huanxiong Xia; Jianhua Liu; Shiquan Lin (Chemical Engineering Journal, 2026)

Improvement of a Large-Scale Circulation Simulation in an Ocean-Sea Ice Model with High Resolution - Yiwen Li; Hailong Liu; Pengfei Lin; Mengrong Ding; Zipeng Yu (Advances in Atmospheric Sciences, 2026)

Efficient Prediction of Fracture Surface Morphology and Analysis of Key Controlling Factors in CAES Tunnel-Type Underground Caverns Based on a Machine Learning Surrogate Model - Shan Lin; Junchen Ding; Wanrui Hu; Guanhua Sun; Jiao Wang; Xianyang Yu; Miao Dong (Rock Mechanics and Rock Engineering, 2026)

In situ-based spectral characteristics of first-year landfast ice in eastern Liaodong Bay, Bohai sea - Qingkang Hou; Yu Yan; Zhikun Lin; Chenchen Yao; Jiayu Ding; Jinghan Xu; Chenyu Shu; Lei Ren; Yingjun Xu (International Journal of Remote Sensing, 2026)

In situ spectral analysis of sea ice contaminated with multiple substances in Liaodong Bay, Bohai Sea - Jinghan Xu; Yu Yan; Zhikun Lin; Qingkang Hou; Jiayu Ding; Chenchen Yao; Lei Ren; Chenyu Shu; Yingjun Xu (Marine Pollution Bulletin, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Phylogeny, species diversity and divergence time of Diaporthe causing leaf blight on Acer palmatum in China - Yu Wan; De-Wei Li; Qiu-Yue Zhang; Yuan-Zhi Si; Jian-Wei Sun; Xiaolei Ding; Lin Huang; Li-Hua Zhu (Fungal Biology, 2026)

Static magnetic field assists corn germination: Changes in nutritional composition and improvement of functional properties - Xin Jiang; Yelinxin Chen; Xiaoxi Yu; Jingwei Wang; Ding Xu; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

Effect of ivarmacitinib on swelling and tenderness in small and large joints and imaging changes in patients with moderate-to-severe RA: a post hoc analysis of a phase III clinical trial - Yuxiang Han; Meng Ding; Shaoxin Cui; Yu Tian; Yushu Yang; Xuying Liu; Lin Yang; Xiaoping Wang; Hongtao Jin; Huifang Guo; Haixue Dai; Shanshan Yin; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular and optical signatures of labile dissolved organic matter during bloom senescence in the Amundsen Sea Polynya - Hui Lin; Qiang Hao; Wei Zhang; Zhenwei Yan; Hao Zhang; Ziming Fang; Yuan Gao; Yong Yu; Ding He (Limnology and Oceanography, 2026)
The Amundsen Sea Polynya (ASP) in the Southern Ocean serves as a potentially significant carbon sink, where phytoplankton blooms drive intense primary production and dissolved organic matter (DOM) cycling. This study focuses on DOM dynamics during the late‐summer bloom phase dominated by Phaeocystis antarctica . Despite the ASP's high productivity, DOM characteristics and their response to bloom senescence remain poorly resolved, limiting insights into carbon sequestration efficiency. We integrated absorbance and fluorescence spectroscopy with Fourier transform ion cyclotron resonance mass spectrometry to analyze seawater samples collected along transects in the ASP during austral summer 2022. Key findings include non‐exponential chromophoric DOM spectra with distinct shoulders at 270–290 nm (aromatic amino acids) and 300–350 nm (mycosporine‐like amino acids), elevated protein‐like fluorescent DOM components linked to P. antarctica degradation, and enrichment of labile, low‐molecular‐weight compounds ( −1 ) amid reduced chlorophyll a (3.81 ± 0.77 mg·m −3 ), indicating DOM release under iron‐replete, nitrate‐limited conditions. This work advances knowledge by identifying unique phytoplankton‐derived DOM signatures that challenge conventional optical metrics like spectral slopes in polar systems, highlighting autochthonous production over terrestrial inputs. Broader implications include improved predictions of carbon cycling in expanding polynyas under climate change, emphasizing reduced sequestration due to labile DOM remineralization and its vulnerability to warming‐induced shifts in Antarctic ecosystems.

Assessment of lateral capacity of semi-rigid monopile for offshore wind turbines in marine clay - Mingke Lin; Changbing Qin; Jiangtao Yi; Yiliang Yu; Xuanming Ding (Ocean Engineering, 2026)

Sorbitol-enhanced butyric acid production in mixed-culture anaerobic fermentation of potato peel waste - Yu Lu; Ke Zheng; Fei Zhao; Lin Ding; Limin Zheng; Jiying Zhu (Journal of Environmental Management, 2026)

Raman-based profiling of microplastics in human uterine tissue: A new dimension in reproductive toxicology - Jingjing Peng; Yaying Lin; Fangfang Yao; Ding Ma; Jinjin Yu; Chunlin Dong (Journal of Environmental Chemical Engineering, 2026)

Insights into the molecular transformation pathways of humus during co-composting of bagasse pith and buffalo manure using compound microorganisms (LXB) - Shiyuan Niu; Binfeng Lin; Yu Zhang; Hongquan Xiang; De Ding; Zhi Huang; Jianbin Li (Journal of Environmental Chemical Engineering, 2026)

Co-addition of alkali lignin and microbial agents drives humic substances assembly by regulating precursor conversion and microbial metabolism in composting - Hongquan Xiang; Shiyuan Niu; De Ding; Binfeng Lin; Yu Zhang; Yongwei Zhu; Shiqiang Li; Ziyang Zhao; Jianbin Li; Zhi Huang (Journal of Environmental Chemical Engineering, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Dorsal Column Nuclei at the Core of TENS: Circuit Principles and Outlook for Neuropathic Pain Therapy - Yi-La Ding; Xue-Qing Wu; Tian-Xin Zhao; Shi-Yao Wang; Ceng-Lin Xu; Bei Tan; Yu Du (Neuroscience Bulletin, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Tilapia skin collagen peptides‑calcium chelates:Structural characterization, stability, in vitro and in vivo anti-osteoporosis mechanism - Xing Xie; Meng-ting Zhang; Chun-lin Huang; Jin-yu Wang; Qiao Ding; Yan-xia Xiong; Zong-cai Tu; Lu Zhang (Food Research International, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Toward circular plastic economy: Conversion of marine waste PET into sustainable bio-based polyesters with carbon negative emissions - Hongtao Ning; Qian Ding; Qiang Zhang; Guiquan Liao; Yujun Chen; Qian Liu; Xiaoqiong Xie; Shimei Xu; Lin Chen; Yu-Zhong Wang; Bo Wu; Jianjun Li (Chemical Engineering Journal, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Seismic performance of steel tubes restrained laminated bamboo columns with different cross-sections - Zicheng Zhang; Yang Wei; Jiawei Chen; Yi Ding; Linjie Huang; Yu Lin (Engineering Structures, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Pivotal effect of oxygen vacancies on S-scheme BiVO4/g-C3N4: Novel dual activation mechanistic studies in photocatalytic selective ethylbenzene oxidation under LED irradiation - Wen-Yu Luo; Ze-Lin Wang; Peng-Jiang Chao; Ying-Ying Xu; Yanfei Xu; Zhuo Li; Lin-Yu Jiao; Mingyue Ding (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Decadal variations in the northern boundary of permafrost in the Xidatan region of the Qinghai-Xizang Plateau: Insights from InSAR and field monitoring - Ju Xin; Luo Jing; Niu Fujun; Yu Fan; Ding Zekun; Yin Guoan; Lin Zhanju; Gao Zeyong (Cold Regions Science and Technology, 2026)

Strategies for Promoting Sustainable Development of Land and Water Resources in a Land Subsidence Affected Area of Taiwan - Chung‐Feng Ding; Yu‐Ching Lin; Reuy‐Chi Kao (Irrigation and Drainage, 2025)
Land subsidence has been observed in many parts of the world. In Taiwan, the main cause is the excessive extraction of groundwater in alluvial plains. For limited land and water resources, it is essential to balance the development among economics, society and conservation issues in land subsidence‐affected areas. The Taiwan government promotes ‘prevention (non‐engineering)’ and ‘reclamation (engineering)’ strategies since the 1980s, which are to increase surface and alternative water supply, decrease groundwater abstraction, strengthen groundwater recharge, enhance enforcement related to water resources utilization and management, reduce induced disasters and encourage public participation. This paper reports the framework of prevention and reclamation strategies and their relative achievements; furthermore, it recently integrated ICT technology with low‐cost devices to monitor the regional pumping behaviour related to land subsidence for groundwater management. The real‐time monitoring system enables the utilization of groundwater more effectively and sustainably in reducing land subsidence. In 2022, according to the delimited goals of each strategy in every phase, all achievements were effective in mitigating the annual subsiding rate and affected area, the former from over 20 cm/year down to 8 cm/year, the latter from 1616 to 310 km 2 .

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The attribution of subseasonal extreme precipitation in arid and semi-arid regions based on extended convergent cross mapping - Tingxing Chen; Attilio Castellarin; Yonghua Zhu; Haishen Lü; Andrea Magnini; Yinghao Fu; Yuan Li; Yu Lin; Zhenzhou Ding; Jiaying Liu (Journal of Hydrology, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Clay sediment adhesion-dominated clogging and its recovery under infiltration washing in statically compacted pervious concrete - Yu Ding; Yapei Xia; Lin Guo; Qi Wan; Zhenyao Xia; Hai Xiao; Yunkang Rao (Journal of Hydrology, 2025)

Microplastic accumulation in endometrial cancer tissues and its metabolic impact - Chunlin Dong; Hongwen Xu; Bing Zhang; Yaying Lin; Jing Song; Jinjin Yu; Ding Ma (Environmental Pollution, 2025)

Synergistic strengthening of 3D‑printed ECC beams through steel-wire mesh and interfaces treatments - Manfang Lin; Yao Ding; Fan Yu; Lingzhi Li; Kequan Yu (Engineering Structures, 2025)

In situ construction of vertical carbon nanosheets on carbon fibers toward high-performance epoxy composites via interfacial enhancement - Na Sun; Bicheng Lin; Quanqing Cui; Qi Zheng; Lu Liu; Chuanshen Wang; Hongliang Ding; Hongfei He; Keqing Zhou; Wei Yang; Bin Yu (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Machine learning-driven prediction of axial capacity of concrete-filled steel tubes columns with built-in bamboo or timber cores - Baoxing Wei; Yang Wei; Jiyang Yi; Jiawei Chen; Yu Lin; Yi Ding (Engineering Structures, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Cholesteric liquid crystal polymer grids enabling facile fabrication of structural color-enhanced electrochromic devices for advanced security encryption with multi-mode display effects - Zhumin Yu; Jin Wang; Lin Li; Zhiyi Guo; Shangjie Liu; Yilei Ding; Mengyue Wu; Changqing Ye (Chemical Engineering Journal, 2025)

Heterologous expression of Pyrenocine A from Colletotrichum gloeosporioides CGMCC 3.17371 - Chao Chen; Yuxin Shi; Haizhifei Ding; Lina Yu; Wei Lin; Jianbin Xiao; Huaidong Zhang; Qin Li; Mingliang Zhang; Li Li (Natural Product Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

IoT-enabled hierarchical thermoelectric nanocomposites for adaptive fire safety systems: Self-powered sensing and threshold-tunable alerts - Chuanshen Wang; Haorui Dun; Lu Liu; Hongliang Ding; Hongfei He; Bicheng Lin; Wenyu Hu; Na Sun; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2025)

Multiscale structural design of heterostructured carbon/boron nitride aerogels for efficient thermal conductivity and broadband electromagnetic wave absorption - Zhengxuan Li; Wang Yang; Chen Zhang; Zhongzhen Ding; Shaoxiong Du; Xi Wu; Junyan Dong; Wenjie Zhu; Sheng Liu; Yu Lin; Lei Liu; Yongfeng Li (Chemical Engineering Journal, 2025)

Forecasting Ocean Mesoscale Eddies in the Northwest Pacific in a Dynamic Ocean Forecast System - Jiakang Zhang; Hailong Liu; Mengrong Ding; Yao Meng; Weipeng Zheng; Pengfei Lin; Zipeng Yu; Yiwen Li; Pengfei Wang; Jian Chen (Journal of Marine Science and Engineering, 2025)
The LICOM Forecast System (LFS), a global eddy-resolving ocean forecasting system, provides 1–15-day forecasts of ocean mesoscale eddies (OMEs). This study conducts a comparative analysis of the forecast results against observational data, thereby evaluating the performance of the LFS. Results show that LFS underestimates the number of eddies by ~10% and their amplitude by ~30%, while overestimating eddy radius by ~5% and velocity by ~25%. Forecasted eddies are matched on a one-to-one basis with observed eddies based on distance, ensuring that those forecasted eddies that can locate corresponding counterparts in the observational dataset yield accurate forecasts. The outcomes reveal that the LFS successfully forecasts 63% of the eddies in the NWP. The characteristics of these accurately forecasted eddies are delineated. The findings indicate that eddies with greater amplitudes are more likely to be accurately predicted. Additionally, we further scrutinized the correlation between eddy attributes and forecast performance, revealing that with an increase in amplitude or a decrease in velocity, the LFS produces forecasts with improved locational accuracy. The mean forecast error in eddy position is 79.94 km for a 1-day lead time, which decreases to 70.97 km for eddies with amplitudes exceeding 1 cm and velocities below 1 km/day.

Recent decline of sea ice area in the Bohai Sea over the period 2001 to 2023 - Zhikun Lin; Yu Yan; Yingjun Xu; Qingkang Hou; Jialin Zhang; Jiayu Ding (Journal of Marine Systems, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Synergistically modulating multiple polarizations of electrically insulating and thermally conductive SnO2@C hollow core–shell nanofasciculi for exceptional EM protection capabilities - Baoxin Fan; Junhao Ding; Shiyang Cai; Kang Fu; Xiangyang Liu; Lingling Lin; Zhenjie Yu; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2025)

Lipid-lowering drug clofibric acid promotes conjugative transfer of RP4 plasmid carrying antibiotic resistance genes by multiple mechanisms - Lin Ding; Chong-Miao Zhang; Hong-Yu Jiang (Journal of Hazardous Materials, 2025)

Milk peptides alleviate irritable bowel syndrome by suppressing colonic mast cell activation and prostaglandin E2 production in mice - Yu Zhang; Zhiqing Lin; Qi Yao; Jian He; Haotian Feng; Wenyi Zhang; Zhigang Liu; Tian Yuan; Xuebo Liu; Long Ding (Food Research International, 2025)

RNA chaperone Hfq promotes the growth of Yersinia enterocolitica in refrigerated foods - Ming Liu; Xinyu Zhao; Zhi Wang; Ling Chen; Zimeng Wang; Huichan Zhai; Congyu Zhou; Huixian Wang; Yu Ding; Jumei Zhang; Xiuhua Lin; Jiahui Zeng; et al. (Food Microbiology, 2025)

Highly transparent, mechanically strong, recyclable, and flame-retardant vanillin-modified poly(urethane-urea) elastomers via dynamic oxime-urethane bonds and hydrogen bonds - Hongliang Ding; Lu Liu; Chuanshen Wang; Na Sun; Lini Wu; Bicheng Lin; Keqing Zhou; Wei Zhang; Xiaodong Qian; Conglin Shi; Bin Yu (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Investigating the main contributors to esterification activity and identifying the aqueous-phase ester synthases in Daqu - Yu Tie; Lin Wang; Bo Ding; Zhao Deng; Qian Yang; Min Zhu; Zhengyun Wu; Lan Tang; Taikei Suyama; Wenxue Zhang (Food Bioscience, 2025)

Two-stage inoculation with lignocellulose-degrading microorganisms in composting: Enhanced humification efficiency and underlying mechanisms - Yu Zhang; Binfeng Lin; Yuhao Hao; Mengling Lu; De Ding; Shiyuan Niu; Hongquan Xiang; Zhi Huang; Jianbin Li (Environmental Research, 2025)

Retraction notice to “Valorization of tropical fruits waste for production of commercial biorefinery products – A review” [Bioresour. Technol. 374 (2023) 128793] - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2025)

Retraction notice to “Production of biochar from tropical fruit tree residues and ecofriendly applications – A review” [Bioresour. Technol. 376 (2023) 128903] - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2025)

Theoretical prediction on supply air performance and CO dilution effect of the pressed-in ventilation system during the construction period - Jie Liu; Lin Xu; Wei Yu; Chao Ding; Kongfei Yu; Shengzhong Zhao; Shao Chen; Longyue Li (Tunnelling and Underground Space Technology, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Insights into nitrogen metabolism and humification process in aerobic composting facilitated by microbial inoculation - Binfeng Lin; Yu Zhang; Yuhao Hao; Mengling Lu; Hongquan Xiang; De Ding; Shiyuan Niu; Kai Li; Jianbin Li; Zhi Huang (Environmental Research, 2025)

Improving synergistic catalysis of CuOx/AgOy/TiO2 for promoting selective catalytic oxidation of ammonia - Junfei Chen; Zhihao Yu; Jinwei Wu; Zhao-Bin Ding; Lin Lang; Lining Fang; Xiuli Yin; Zebao Rui (Chemical Engineering Journal, 2025)

Sustainable and selective upgrade of Cu(II) to High-Value HKUST-1 from acidic electroplating wastewater - Lin Ding; Qiang Wang; Yu Luo; Yunxia Luo; Wei Ren; Hui Shi; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

GRACE/ML-based analysis of the spatiotemporal variations of groundwater storage in Africa - Kuiyuan Ding; Xiaowei Zhao; Jianmei Cheng; Ying Yu; Yiming Luo; Joaquin Couchot; Kun Zheng; Yihang Lin; Yanxin Wang (Journal of Hydrology, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Role of C/EBP Homologous Protein in Vascular Stenosis After Carotid Artery Injury - Lin Teng; Qin Qin; Zi-yi Zhou; Fei Zhou; Cun-yu Cao; Chao He; Jia-wang Ding; Jian Yang (Biochemical Genetics, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Impacts of model resolution on the simulation of sea-level variability by a global ocean-sea ice model - Yaqi Wang; Hailong Liu; Zipeng Yu; Pengfei Lin; Mengrong Ding (Climate Dynamics, 2025)

High-rate bridge displacement monitoring with low-rate virtual reference station data - Xuanyu Qu; Xiaoli Ding; Wenkun Yu; Xinrui Li; You-Lin Xu (GPS Solutions, 2025)
We present a new Global Navigation Satellite Systems (GNSS) positioning approach that utilizes low-rate Virtual Reference Station (VRS) data to achieve high-rate displacement monitoring. The method integrates tightly the VRS technology with asynchronous Real-Time Kinematic (RTK) method to overcome the limitation of VRS in high-rate structural health monitoring (SHM) applications. When this approach is used, no local reference station is required so that the efforts and cost of setting up reference stations can be avoided. Experiments with datasets from a controlled shaking platform and a long-span bridge in Hong Kong with both temperature and typhoon excitations have indicated that the proposed approach worked effectively. The results demonstrated that when a baseline exceeded about 3 km, the vertical errors of RTK GNSS positioning could be up to about 15.9 mm (standard deviations), insufficient for most SHM applications. In this case, the proposed method enhanced the accuracy by about 60% to 6.0 mm when using VRS data openly available in Hong Kong. The accuracy achieved was equivalent to that of RTK positioning using a 1.2 km baseline. The shaking platform trial demonstrated that the monitoring station could be up-sampled to 100 Hz without a noticeable loss in accuracy. The proposed method could capture precisely the peak frequencies and amplitudes of vibrations, with errors as low as 0.001 Hz and 0.1 mm. This method broadens the applicability of GNSS positioning in SHM applications.

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Genetic diversity analysis of Saccharosydne procerus in Hunan region, China - Lian Shan; Yu Wu; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Lin Qiu; Youzhi Li (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Loss prediction of carbon stocks caused by Spartina alterniflora clearing in coastal wetlands of Yancheng, China - Mengyuan Su; Yufeng Li; Chunqi Qiu; Yong Zhou; Lin Li; Yue Jia; Jingjing Ding; Zhaoyuan Yu; Alan Wright; Hongyu Liu (Geo-Marine Letters, 2024)

PFOS impairs cardiac function and energy metabolism under high-fat diet: Insights into role of circulating macrophage emphasized by exposure distribution - Ze Zhang; Hao Yin; Chuer Zheng; Zhenhua Yu; Rifat Zubair Ahmed; Yong Niu; Chengying Zhou; Jian Ding; Huan Lin; Yongfeng Lin; Yuxin Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

Combined effects of thermal environment and gene regulation on metabolic enzyme activities of major metabolic tissues in a winter-breeding amphibian - Chi-Ying Zhang; Hua-Li Hu; Yu Wang; Lin Zhang; Guo-Hua Ding (Journal of Thermal Biology, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Deep mineralization of bisphenol A via Cu–Mn spinel oxide nanospheres anchored N-doped carbon activated peroxymonosulfate - Xiaobo Wang; Lin He; Yu Zhou; Nan Wang; Lihua Zhu; JunTao Yan; Deng Ding; Wenjun Zhu; Xiaohua Zuo; Jinpeng Wang; Xiaoyong Wu (Chemical Engineering Journal, 2024)

Neural substrates for regulating self-grooming behavior in rodents - Guanqing Li; Chanyi Lu; Miaomiao Yin; Peng Wang; Pengbo Zhang; Jialiang Wu; Wenqiang Wang; Ding Wang; Mengyue Wang; Jiahan Liu; Xinghan Lin; Jian-Xu Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Engineering Au-Pt atomic alloy cocatalysts for enhanced H2 production from photo-reforming of lignocellulosic biomass wastes - Fangjie Ding; Hongbo Yu; Renyong Tu; Sha Li; Lin Chen; Bing Li; Jianzhong Guo; Chunzheng Wu (Chemical Engineering Journal, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Atomically precise gold nanoclusters as ROS-scavenging clusterzymes to treat high-fat diet-induced obesity - Jialuo Ding; Mengyuan Zhao; Yeying Li; Kexin Zhang; Hanxing Chen; Xinying Hu; Le Li; Yu Su; Xun Yuan; Zhenkun Lin (Chemical Engineering Journal, 2024)

Important role of Bacillus subtilis as a probiotic and vaccine carrier in animal health maintenance - Chunmei Yuan; Xiang Ji; Yuyu Zhang; Xinli Liu; Luogang Ding; Jianda Li; Sufang Ren; Fei Liu; Zhi Chen; Lin Zhang; Wenxing Zhu; Jiang Yu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Lateral holding behaviour of torpedo piles in spatially variable soil: Development of a probabilistic design approach - Jiang Tao Yi; Shi Jie Xu; Wu Hao Liu; Lin Ding; Zhen Wang; Hong Yu Tang; Xiao Bin Li (Computers and Geotechnics, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

A simple numerical simulation model can elucidate the key factors for designing a miniaturized ion trap mass spectrometer - Xinming Huo; Lin Gan; Xinyue Ding; Quan Yu; Bin Zhou; Jianhua Zhou; Xiang Qian (Analytica Chimica Acta, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Evaluating westward and eastward propagating mesoscale eddies using a 1/10° global ocean simulation of CAS-LICOM3 - Mengrong Ding; Hailong Liu; Pengfei Lin; Yao Meng; Zipeng Yu (Ocean Modelling, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Effects of warming on greenhouse gas emissions from China’s rice paddies - Nan Zhang; Lin Wang; Xueni Wang; Zhuoshu Liu; Shan Huang; Zihao Wang; Changqing Chen; Haoyu Qian; GangHua Li; Zhenghui Liu; Yanfeng Ding; Weijian Zhang; et al. (Agriculture, Ecosystems & Environment, 2024)

Managing carbon emissions in urban mobility system: A credit-based reservation scheme - Lin Yu; Yanyan Ding; Sisi Jian (Transportation Research Part D: Transport and Environment, 2024)

Metabolic disturbance of short- and medium-chain chlorinated paraffins to zebrafish larva - Shuangshuang Chen; Xiaoqian Ren; Ying Yu; Lin Cheng; Guanghui Ding; Hairong Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Machine learning prediction for constructing a universal multidimensional information library of Panax saponins (ginsenosides) - Hongda Wang; Lin Zhang; Xiaohang Li; Mengxiao Sun; Meiting Jiang; Xiaojian Shi; Xiaoyan Xu; Mengxiang Ding; Boxue Chen; Heshui Yu; Zheng Li; Dean Guo; et al. (Food Chemistry, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

An in-situ combo Mo-based ionic liquid and SAPO-11 catalyst for efficient biolipids hydrodeoxygenation and isomerization - Yongxin Ding; Jun Lin; Panjie Yu; Hongwei Zhang; Yongde Ma; Zhenping Cai; Yanning Cao; Kuan Huang; Lilong Jiang (Fuel, 2024)

Visible light-mediated supramolecular framework for tunable CO2 adsorption - Tao Yang; Chunyi Yu; Chen Gu; Yang Liu; Hui Wen; Xiao-Qin Liu; Guoliang Liu; Lifeng Ding; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Wet peroxide oxidation process catalyzed by Cu/Al2O3: phenol degradation and Cu2+ dissolution behavior - Wumin Zhang; Huimin Zhuang; Yu Guo; Hua Chi; Qiuyue Ding; Lu Wang; Yanyan Xi; Xufeng Lin (Environmental Science and Pollution Research, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Anti-CD20 treatment attenuates Th2 cell responses: implications for the role of lung follicular mature B cells in the asthmatic mice - Jilong He; Jingling Li; Qibin Lin; Haiyang Ni; Sisi Huang; Hong Cheng; Xuhong Ding; Yi Huang; Hongying Yu; Yaqing Xu; Hanxiang Nie (Inflammation Research, 2024)

Reef effect of vertical relief on the shelter-seeking and foraging processes of juvenile fat greenling (Hexagrammos otakii) in a mesocosm experiment - Yue Zhang; Tao Sun; Gang Ding; Bo Li; Shuhan Li; Wei Yang; Daode Yu; Xiaoling Wang; Qianzhao Sun; Haiying Lin (Applied Animal Behaviour Science, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Effects of shore-normal coastal structure on medium- to long-term embayed shoreline evolution - Jitao Yu; Yuanting Ding; Pei Liu; Renfu Fan; Lin Zhang (Acta Oceanologica Sinica, 2024)

Group VIII metal difluorocarbene complexes: Synthesis and applications - Xue Ding; Yu-Fei Yao; Weikang Lin; Zhengqing Ye; Cheng-Pan Zhang (Journal of Fluorine Chemistry, 2024)

Cheap organocatalyst diphenyl phosphate for efficient chemical recycling of poly(lactic acid), other polyesters and polycarbonates - Wanhua Wu; Huajuan Zhai; Kaiting Wu; Xin Wang; Weihan Rao; Jiandong Ding; Lin Yu (Chemical Engineering Journal, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

3D printing of customizable and lightweight multilayer MXene/nanocellulose architectures for tunable electromagnetic interference shielding via direct ink writing - Lei Chen; Tian Mai; Xing-Xiang Ji; Pei-Lin Wang; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Thermally activated delayed fluorescence emitters with bulky four-coordinate boron acceptors for high-performance solution-processed OLEDs - Bowen Li; Zhenming Ding; Zhimin Wu; Meihua Liu; Shaofeng Chen; Dongcheng Chen; Zhigao Li; Long Sang; Yu Liu; Lili Lin; Weiguo Zhu; Xiaobo Wan (Chemical Engineering Journal, 2023)

Response of topsoil Fe-bound organic carbon pool and microbial community to Spartina alterniflora invasion in coastal wetlands - Meifen Lin; Yu Chen; Liwen Cheng; Yi Zheng; Weiqi Wang; Jordi Sardans; Zhaoliang Song; Georg Guggenberger; Yuanchun Zou; Xueli Ding; Akash Tariq; Fanjiang Zeng; et al. (CATENA, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Prevalence of antimicrobial resistance in a full-scale drinking water treatment plant - Qihui Gu; Tao Lin; Xianhu Wei; Youxiong Zhang; Shi Wu; Xiaojuan Yang; Hui Zhao; Chufang Wang; Juan Wang; Yu Ding; Jumei Zhang; Qingping Wu (Journal of Environmental Management, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Monitoring regional soil organic matter content using a spatiotemporal model with time-series synthetic Landsat images - Mei-Wei Zhang; Xiao-Qing Wang; Xiao-Gang Ding; Hua-Lei Yang; Qian Guo; Ling-Tao Zeng; Yu-Pei Cui; Xiao-Lin Sun (Geoderma Regional, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Regulating catalytic stability of PtSnM/CeO2 (M = Mn, W, Nb) catalysts via the closely coupled multi-active sites to promote multicomponent VOCs oxidation - Ruyi Gao; Xinrong Tian; Xinlei Ding; Zhiquan Hou; Zeya Li; Xiaohui Yu; Jia Wang; Linke Wu; Lin Jing; Jiguang Deng; Yuxi Liu; Hongxing Dai (Chemical Engineering Journal, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

High-resolution imaging of O2 dynamics and metal solubilization in the rhizosphere of the hyperaccumulator Leersia hexandra Swartz - Yao He; Na Ding; Guo Yu; Geoffrey I. Sunahara; Hua Lin; Xuehong Zhang; Habib Ullah; Jie Liu (Journal of Hazardous Materials, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Erosion hotspot identified along the sandy coast of Shanwei: characteristics and origin - Jitao Yu; Yuanting Ding; Lin Zhang; Pei Liu; Renfu Fan (Acta Oceanologica Sinica, 2023)

Experimental study on vertical temperature distribution of the two-layer smoke flow in tunnel during construction - Lin Xu; Mingxuan Qiu; Yinghao Zhao; Chao Ding; Wei Yu; Shengzhong Zhao; Longyue Li; Jie Liu (Tunnelling and Underground Space Technology, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

Thermosensitive nanocomposite hydrogel composed of PVPylated poly(D,L-alanine) and laponite as an injectable and bioactive biomaterial - Siyi Gu; Hancheng Wang; Yaoben Wang; Xin Wang; Xin Liu; Yang Wang; Peng Liu; Jiandong Ding; Lin Yu (Chemical Engineering Journal, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Retraction Note: MicroRNA-20b suppresses the expression of ZFP-148 in viral myocarditis - Hong-Fei Xu; Xiang-Ting Gao; Jun-Yi Lin; Xue-Hua Xu; Jun Hu; Yu-Jie Ding; Shao-Hua Zhu (Molecular and Cellular Biochemistry, 2023)

Identification and genomic characterization of Ralstonia pseudosolanacearum strains isolated from pepino melon in China - Shanwen Ding; Lin Yu; Guobing Lan; Yafei Tang; Zhenggang Li; Zifu He; Xiaoman She (Physiological and Molecular Plant Pathology, 2023)

Bilayer metal-organic frameworks/MXene/nanocellulose paper with electromagnetic double loss for absorption-dominated electromagnetic interference shielding - Tian Mai; Wen-Yan Guo; Pei-Lin Wang; Lei Chen; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

RETRACTED: Production of biochar from tropical fruit tree residues and ecofriendly applications – A review - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Field experiments on quantifying the contributions of Coreopsis canopies and roots to controlling runoff and erosion on steep loess slopes - Yu-wei Gong; Hai-jun Yu; Pei Tian; Wen-zhao Guo; Lin Chen; Ding-tao Shen (Journal of Mountain Science, 2023)

Remarkable adsorption capacity of Cu2+-doped ZnAl layered double hydroxides and the calcined materials toward phosphate - Ding Ling Gao; Wei Wei Lin; Qiao Jing Lin; Fei Fei Dai; Yan Xue Xue; Jian Hua Chen; Yu Xiang Liu; Yang Huang; Qian Yang (Journal of Environmental Chemical Engineering, 2023)

Direct conversion of water to hydrogen peroxide on single electrode towards partial oxidation of propylene - Runfei Xu; Haoyang Huang; Wenjing Wang; Lei Ding; Qiang Lin; Jinbing Li; Yu Zhang; Yongsheng Han; Jianguo Wang; Xiaohua Lu (Chemical Engineering Journal, 2023)

RETRACTED: Valorization of tropical fruits waste for production of commercial biorefinery products – A review - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Real-time outlier detection in integrated GNSS and accelerometer structural health monitoring systems based on a robust multi-rate Kalman filter - Xuanyu Qu; Xiaoli Ding; You-Lin Xu; Wenkun Yu (Journal of Geodesy, 2023)

Moderate relative size of covered and non-covered structures of artificial reef enhances the sheltering effect on reef fish - Yue Zhang; Tao Sun; Gang Ding; Daode Yu; Wei Yang; Qianzhao Sun; Xiaoling Wang; Haiying Lin (Frontiers in Marine Science, 2023)
Identifying the relationship between fish aggregations and artificial reefs (ARs) is important for optimizing reef structures and protecting marine resources subjected to external disturbance. Yet, knowledge remains limited of how the distribution of fish is affected by shelter availability provided by different AR structures. Here, we tested the effects of two structural attributes on the distribution of a benthic juvenile reef fish (fat greenling, Hexagrammos otakii ). We used a laboratory mesocosm experiment with a simplified reef unit that was made of covered structure and non-covered structure. The covered structure was defined as the area inside ARs that provided effective shelter. The non-covered structure was defined as the area along the edge of ARs, which attracts fish but has lower sheltering effects. Four scenarios of two orthogonal structural attributes contained in a reef unit were implemented: size of covered structure (small shelter versus large shelter) and size of non-covered structure (small edge versus large edge), forming three size ratios of shelters to edges (low, medium, and high). The sheltering effects of the four scenarios were evaluated based on changes to the distribution patterns of fish under disturbance. We found that the reef with a large shelter had a better sheltering effect than the reef with a small shelter, but was limited by its small edge, especially when fish density was high. In contrast, the sheltering effect of the reef with a small shelter was limited by its large edge compared to the small edge. Thus, a moderate shelter-edge ratio enhanced the ability of juvenile fat greenling to elude external disturbance. Our findings highlight the importance of quantifying how the structural composition of reefs affects fish distributions, providing guidance to optimize AR structures.

The thermal degradation and soil recovery of thermal treatment of field-weathered decabrominated diphenyl ether-contaminated soil - Jennifer Ia Wen Wen Liu; Yu-Jie Lin; Chi-Fong Ko; Jiann-yuan Ding; Yang-hsin Shih (Chemosphere, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Nanosphere-structured hierarchically porous PVDF-HFP fabric for passive daytime radiative cooling via one-step water vapor-induced phase separation - Ningbo Cheng; Dongyang Miao; Chao Wang; Yanyan Lin; Aijaz Ahmed Babar; Xianfeng Wang; Zhaohui Wang; Jianyong Yu; Bin Ding (Chemical Engineering Journal, 2023)

Optimization of bovine embryonic fibroblast feeder layer prepared by Mitomycin C - Fang Zhao; Jianning Yu; Qiang Ding; Kunlin Chen; Shuwen Xia; Yong Qian; Yundong Gao; Zhiping Lin; Huili Wang; Jifeng Zhong (Cell and Tissue Banking, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Modulation of the interfacial charge density on Fe2P–CoP by coupling CeO2 for accelerating alkaline electrocatalytic hydrogen evolution reaction and overall water splitting - Xueda Ding; Jie Yu; Weiqiao Huang; Dongyang Chen; Wei Lin; Zailai Xie (Chemical Engineering Journal, 2023)

Uncertainty in Atlantic Multidecadal Oscillation derived from different observed datasets and their possible causes - Bowen Zhao; Pengfei Lin; Aixue Hu; Hailong Liu; Mengrong Ding; Zipeng Yu; Yongqiang Yu (Frontiers in Marine Science, 2022)
As a leading mode of sea surface temperature (SST) variability over the North Atlantic in both observations and model simulations, the Atlantic Multidecadal Oscillation (AMO) can have a substantial influence on regional and global climate. By using Low-Frequency Component Analysis, we explore the uncertainties of the resulting AMO indices and the corresponding spatial patterns derived from three observational SST datasets. We found that the known coherent spatial pattern of the AMO at the basin scale over the North Atlantic appears in two out of the three datasets. Further analysis indicates that both the warming trend and the different techniques used to construct these observed gridded SSTs contribute to the AMO’s spatial coherence over the North Atlantic, especially during periods of sparse data sampling. The SST in the Extended Reconstructed SST dataset version 5 (ERSSTv5), changes from being systematically below the other datasets during the dense sampling periods on either side of the Second World War (WWII), to systematically above the other datasets during WWII, thereby introducing an artificial 10–20-year variability that affects the AMO’s spatial coherence. This coherence in the AMO’s spatial pattern is also affected by bias adjustment in ERSSTv5 at relative cool (i.e., non-summer) seasons, and by the heterogeneous North Atlantic warming pattern. The different AMO patterns can induce the different effects of wind, surface heat fluxes, and then drive ocean circulation and its heat transport convergence, especially for some seasons. For AMO indices, both the different detrending methods and different observational data result in uncertainty for the period 1935–1950. Such SST uncertainty is important to detect the relative role of the atmosphere and ocean in shaping the AMO.

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Optimizing the Wheat Seeding Rate for Wide-Space Sowing to Improve Yield and Water and Nitrogen Utilization - Zhixin Wang; Shahbaz Khan; Min Sun; Aixia Ren; Wen Lin; Pengcheng Ding; Hafeez Noor; Shaobo Yu; Yu Feng; Qiang Wang; Zhiqiang Gao (International Journal of Plant Production, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Photosynthetic compensation of non-leaf organ stems of the invasive species Sphagneticola trilobata (L.) Pruski at low temperature - Min-ling Cai; Wen-qiao Ding; Jun-jie Zhai; Xiao-ting Zheng; Zheng-chao Yu; Qi-lei Zhang; Xiao-hua Lin; Wah Soon Chow; Chang-lian Peng (Photosynthesis Research, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Quantitative characterization of horizontal well production performance with multiple indicators: a case study on the Weiyuan shale gas field in the Sichuan Basin, China - Rongze Yu; Wei Guo; Lin Ding; Meizhu Wang; Feng Cheng; Xiaowei Zhang; Shangwen Zhou; Leifu Zhang (Frontiers of Earth Science, 2021)

Geological and climatic histories likely shaped the origins of terrestrial vertebrates endemic to the Tibetan Plateau - Jiekun He; Siliang Lin; Chenchen Ding; Jiehua Yu; Haisheng Jiang (Global Ecology and Biogeography, 2021)
Aim The Tibetan Plateau (TP) hosts many endemic species, but questions regarding when and from where these species originated have not been comprehensively answered. Here, we provide a synthesis of the biogeographical history of terrestrial vertebrates endemic to the TP and investigate the potential drivers of their spatio‐temporal origins. Location Tibetan Plateau and its surrounding regions. Time period Cenozoic. Major taxa studied Terrestrial vertebrates. Methods We used dispersal–extinction–cladogenesis models based on time‐calibrated phylogenies to reconstruct the ancestral ranges of 174 endemic TP species and compiled the ancestral ranges and age estimates of their dispersal events. We generated a possibility map of source areas for endemic TP species by counting the incidence of non‐TP sister clades in 110 km × 110 km grid cells. We used generalized linear mixed models to assess the relative importance of historical processes and environmental factors in explaining the geographical variations in the source areas. We created subsets based on four vertebrate classes to test whether the dispersal events varied spatially and temporally among taxonomic groups. Results We found that the endemic species colonized the TP as early as 55 Ma, and that the main colonization phase started to increase around 15 Ma and peaked after 6 Ma. The major source areas of endemic TP species include the Hengduan Mountains, the Himalayas, and Central Asia. Elevation difference had the strongest effect on the source areas, followed by geographical distance. The spatio‐temporal origins of species endemic to the TP and the potential drivers showed significant differences among vertebrate classes. Main conclusions Our study supports the hypothesis that endemic TP species originated from various zoogeographical regions at different times and highlights the important roles of the TP uplift and past climatic changes for determining the spatio‐temporal origins of endemic TP species.

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

A Fluorescent “Turn-off” Probe for the Determination of Curcumin Using Upconvert Luminescent Carbon Dots - Chenhong Yu; Qi Zhuang; Hanyue Cui; Li Li; Yaping Ding; Jiaxin Lin; Yingchun Duan (Journal of Fluorescence, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Eddy-resolving Simulation of CAS-LICOM3 for Phase 2 of the Ocean Model Intercomparison Project - Yiwen Li; Hailong Liu; Mengrong Ding; Pengfei Lin; Zipeng Yu; Yongqiang Yu; Yao Meng; Yunlong Li; Xiaodong Jian; Jinrong Jiang; Kangjun Chen; Qian Yang; et al. (Advances in Atmospheric Sciences, 2020)
A 61-year (1958–2018) global eddy-resolving dataset for phase 2 of the Ocean Model Intercomparison Project has been produced by the version 3 of Chinese Academy of Science, the State Key Laboratory of Numerical Modeling for Atmospheric Sciences and Geophysical Fluid Dynamics/Institute of Atmospheric Physics (LASG/IAP) Climate system Ocean Model (CAS-LICOM3). The monthly and a part of the surface daily data in this study can be accessed on the Earth System Grid Federation (ESGF) node. Besides the details of the model and experiments, the evolutions and spatial patterns of large-scale and mesoscale features are also presented. The mesoscale features are reproduced well in the high-resolution simulation, as the mesoscale activities can contribute up to 50% of the total SST variability in eddy-rich regions. Also, the large-scale circulations are remarkably improved compared with the low-resolution simulation, such as the climatological annual mean SST (the RMSE is reduced from 0.59°C to 0.47°C, globally) and the evolution of Atlantic Meridional Overturning Circulation. The preliminary evaluation also indicates that there are systematic biases in the salinity, the separation location of the western boundary currents, and the magnitude of eddy kinetic energy. All these biases are worthy of further investigation.

FGOALS-g3 Model Datasets for CMIP6 Flux-Anomaly-Forced Model Intercomparison Project - Yaqi Wang; Zipeng Yu; Pengfei Lin; Hailong Liu; Jiangbo Jin; Lijuan Li; Yanli Tang; Li Dong; Kangjun Chen; Yiwen Li; Qian Yang; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) is an endorsed Model Intercomparison Project in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The goal of FAFMIP is to investigate the spread in the atmosphere-ocean general circulation model projections of ocean climate change forced by increased CO 2 , including the uncertainties in the simulations of ocean heat uptake, global mean sea level rise due to ocean thermal expansion and dynamic sea level change due to ocean circulation and density changes. The FAFMIP experiments have already been conducted with the Flexible Global Ocean-Atmosphere-Land System Model, gridpoint version 3.0 (FGOALS-g3). The model datasets have been submitted to the Earth System Grid Federation (ESGF) node. Here, the details of the experiments, the output variables and some baseline results are presented. Compared with the preliminary results of other models, the evolutions of global mean variables can be reproduced well by FGOALS-g3. The simulations of spatial patterns are also consistent with those of other models in most regions except the North Atlantic and the Southern Ocean, indicating large uncertainties in the regional sea level projections of these two regions.

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Erratum to: LICOM Model Datasets for the CMIP6 Ocean Model Intercomparison Project - Pengfei Lin; Zipeng Yu; Hailong Liu; Yongqiang Yu; Yiwen Li; Jinrong Jiang; Wei Xue; Kangjun Chen; Qian Yang; Bowen Zhao; Jilin Wei; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)

Mechanisms behind soil N dynamics following cover restoration in degraded land in subtropical China - Xiangzhou Zheng; Cheng Lin; Baoling Guo; Juhua Yu; Hong Ding; Shaoyun Peng; Jinbo Zhang; Eric Ireland; Deli Chen; Christoph Müller; Yushu Zhang (Journal of Soils and Sediments, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

LICOM Model Datasets for the CMIP6 Ocean Model Intercomparison Project - Pengfei Lin; Zhipeng Yu; Hailong Liu; Yongqiang Yu; Yiwen Li; Jirong Jiang; Wei Xue; Kangjun Chen; Qian Yang; Bowen Zhao; Jilin Wei; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The datasets of two Ocean Model Intercomparison Project (OMIP) simulation experiments from the LASG/IAP Climate Ocean Model, version 3 (LICOM3), forced by two different sets of atmospheric surface data, are described in this paper. The experiment forced by CORE-II (Co-ordinated Ocean–Ice Reference Experiments, Phase II) data (1948–2009) is called OMIP1, and that forced by JRA55-do (surface dataset for driving ocean–sea-ice models based on Japanese 55-year atmospheric reanalysis) data (1958–2018) is called OMIP2. First, the improvement of LICOM from CMIP5 to CMIP6 and the configurations of the two experiments are described. Second, the basic performances of the two experiments are validated using the climatological-mean and interannual time scales from observation. We find that the mean states, interannual variabilities, and long-term linear trends can be reproduced well by the two experiments. The differences between the two datasets are also discussed. Finally, the usage of these data is described. These datasets are helpful toward understanding the origin system bias of the fully coupled model.

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Evaluation of the diagnostic ratios of adamantanes for identifying seriously weathered spilled oils from simulated experiment and actual oil spills - Bin Han; Li Zheng; Qian Li; Faxiang Lin; Yu Ding (Environmental Geochemistry and Health, 2019)

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

Characterization of milk protein composition of the Yangtze finless porpoise - Xianyuan Zeng; Minmin Chen; Zhigang Liu; Daoping Yu; Shiang‐Lin Huang; Jiwei Yang; Fei Fan; Ding Wang; Yujiang Hao; Ghulam Nabi (Marine Mammal Science, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Assessment of anti-diabetic activity of peanut shell polyphenol extracts - Xiao-meng Sun; Hai-qing Ye; Jing-bo Liu; Lei Wu; Ding-bo Lin; Ya-li Yu; Feng Gao (Journal of Zhejiang University-SCIENCE B, 2018)

Pseudomonas pharmafabricae sp. nov., Isolated From Pharmaceutical Wastewater - Xiao-Yun Yu; Jing-Yu Zhai; Chen Wu; Chong-Ya Zhang; Jie-Ying Shi; Lin-Xian Ding; Min Wu (Current Microbiology, 2018)

Berberine protects renal tubular cells against hypoxia/reoxygenation injury via the Sirt1/p53 pathway - Yuanbang Lin; Mingwei Sheng; Yijie Ding; Nan Zhang; Yayue Song; Hongyin Du; Ning Lu; Wenli Yu (Journal of Natural Medicines, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

Dcf1 Triggers Dendritic Spine Formation and Facilitates Memory Acquisition - Qiang Liu; Ruili Feng; Yu Chen; Guanghong Luo; Huang Yan; Ling Chen; Rongfei Lin; Yuqiang Ding; Tieqiao Wen (Molecular Neurobiology, 2018)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

RETRACTED ARTICLE: MicroRNA-20b suppresses the expression of ZFP-148 in viral myocarditis - Hong-Fei Xu; Xiang-Ting Gao; Jun-Yi Lin; Xue-Hua Xu; Jun Hu; Yu-Jie Ding; Shao-Hua Zhu (Molecular and Cellular Biochemistry, 2017)

Both major and minor QTL associated with plant height can be identified using near-isogenic lines in maize - Xiaoyu Ding; Xun Wu; Lin Chen; Chunhui Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Zhizhai Liu; Yong-xiang Li (Euphytica, 2017)

Analysis of QTL for seed oil content in Brassica napus by association mapping and QTL mapping - Ying Fu; Dongqing Zhang; Madeleine Gleeson; Yaofeng Zhang; Baogang Lin; Shuijin Hua; Houdong Ding; Martin Frauen; Jiana Li; Wei Qian; Huasheng Yu (Euphytica, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Population geography in China since the 1980s: Forging the links between population studies and human geography - Yu Zhu; Jinhong Ding; Guixin Wang; Jianfa Shen; Liyue Lin; Wenqian Ke (Journal of Geographical Sciences, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Wave pressure acting on V-shaped floating breakwater in random seas - Yang Yu; Ning Ding; Jie Lin; Jiajia Hou (Journal of Ocean University of China, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Novel differential transcript expression identified by LongSAGE in the mouse endometrium during the implantation window - Yu-Bin Ding; Jun-Lin He; Xue-Mei Chen; Xue-Qing Liu; Ying-Xiong Wang (Molecular Biology Reports, 2013)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Individual Management of Recurrent Intracranial Aneurysms: The Wuxi Experience - Lin Yu-chang; Santosh Kesari; Leng Bing; Ding Ya-suo; Pang Ming-zhi (Cell Biochemistry and Biophysics, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Preparation of high-affinity rabbit monoclonal antibodies for ciprofloxacin and development of an indirect competitive ELISA for residues in milk - Bin Huang; Yun Yin; Lei Lu; Hai Ding; Lin Wang; Ting Yu; Jia-jin Zhu; Xiao-dong Zheng; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

Seroepidemiology of Toxoplasma gondii in pet dogs and cats in Beijing, China - Jinhai Yu; Jun Ding; Zhaofei Xia; Degui Lin; Yili Li; Junying Jia; Qun Liu (Acta Parasitologica, 2008)
Sera from 534 pet dogs and 335 pet cats from Beijing (China) were tested for anti-Toxoplasma gondii antibodies using an enzyme-linked immunosorbent assay or the latex agglutination test. The seropositivity by year, season, sex and age was analysed. Overall, 128 dogs (24.0%) and 50 cats (14.9%) had antibodies to T. gondii. When analysed by season, the highest seroprevalence was found in spring for dogs (31.3%) and cats (25.1%), and the differences in seroprevalence by season was statistically significant in cats (P

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)